The Effects of Physical Exercises Using VertiMax for Developing Strength Defined By Speed and Some Physiological Indicators and Offensive Skills In Young Basketball Players - Sami, Luay (Journal of Physical Education, 2017)
The problem lies in weakness in physical abilities that negatively affected physiological indicators and offensive skills. This weakness comes as a result of not using modern training devices or exercises that are similar to offensive skills. The research aimed at designing special exercises using vertimax for developing strength defined by speed for arms and legs as well as identifying the effects of these exercises on the development of some physiological indicators and offensive skills of basketball. The researchers hypothesized significant effect of special physical exercises using vertimax on the development of power defined by speed of arms and legs as well as physiological indicators and offensive skills of young basketball players. The subjects were (10) young basketball players from the national center for gifted in basketball from 23/6/2017 – 2/9/2017. The data was collected and treated using proper statistical operations to conclude that developing strength defined by speed led to great development in physiological indicators and offensive skills in young basketball players. Finally the researcher recommended selecting physical exercises with different resistance according to motor pathway of basketball offensive skills in a matter that suits the sports’ physical ,skill and physiological requirements